Loss Aversion and Adaptation in the Labor Market: Empirical Indifference Functions and Labor Supply - Dunn, L. F. (The Review of Economics and Statistics, 1996)
This paper presents empirically determined indifference functions for income and leisure which exhibit the phenomena of loss aversion and a utility reference point determined by adaptation, as expounded by Kahneman and Tversky and others. Data for this study were gathered in original surveys of seven diverse labor markets. The indifference functions of all show common features consistent with loss aversion/adaptation. These features help explain stability in labor markets in the face of an overtime premium which prevents the many workers in the United States from being at an optimal equilibrium and causes discontinuities in labor supply curves. Labor supply curves derived from indifference curves with the loss aversion adaptation features have much smaller discontinuities than those based on simulated curves without these features. Copyright 1996 by MIT Press.